Women Underrepresentation in Editorial Boards of Geology Journals and the Utopia of Gender Equality - Henriques, M. H.; Garcia, L. F. (Frontiers in Earth Science, 2022)
The 5th goal of the 2030 Agenda for Sustainable Development aims at promoting gender equality and empowering all women and girls at all levels of decision making. This includes editorial decisions in the frame of the dissemination of scientific knowledge as a result of research and development activities. This work analyses the women representation in the editorial boards of 53 subscription or open access geology journals of all quartile rankings included in the Web of Science Core Collection™ in 2020 in order to assess how far female geoscientists are from the 2030 Agenda targets concerning gender equality. Among the analyzed journals, in 85% the position of editor(s)-in-chief is (are) occupied by a man or a group of men, and in the remaining 15% by women. Moreover, 80% of the people that make up the editorial board of the same journals are men and 20% are women. Only one journal indicates the editor(s)-in-chief gender and the number of members per gender that make up the editorial board. The strong gender gap detected in this study shows that the goal of gender equality in the editorial boards of geological journals still remains a long way off, and publishers should therefore increase gender diversity in editorial teams and referee pools.